2021
DOI: 10.1097/j.jcrs.0000000000000470
|View full text |Cite
|
Sign up to set email alerts
|

Results of thin-cap small-incision lenticule extraction

Abstract: Purpose: To evaluate the influence of a thin cap in small-incision lenticule extraction (SMILE) for the correction of myopia or myopic astigmatism. Setting: Tertiary care private practice. Methods: A chart review of 102 eyes of 51 patients was performed. The effect of 120 µm vs 100 μm cap thickness on postoperative spherical equivalent refraction (SEQ), cylinder, corrected and uncorrected visual acuities, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Choosing a thin cap over the extracted lenticule may be an option to preserve more residual stromal thickness. 5 The mesopic pupil size of this patient is rather large as is typical for young women. However, large pupils are not associated with dysphotopsia if the lenticule diameter (or effective optical zone in LASIK) is 6.5 mm or larger.…”
Section: H Burkhard Dick MD Phd Febos-cr Suphi Taneri Md Febos-crmentioning
confidence: 68%
“…Choosing a thin cap over the extracted lenticule may be an option to preserve more residual stromal thickness. 5 The mesopic pupil size of this patient is rather large as is typical for young women. However, large pupils are not associated with dysphotopsia if the lenticule diameter (or effective optical zone in LASIK) is 6.5 mm or larger.…”
Section: H Burkhard Dick MD Phd Febos-cr Suphi Taneri Md Febos-crmentioning
confidence: 68%
“…Liu et al ( 12 ) have demonstrated that a 110-μm cap thickness had better visual outcomes postoperatively compared with a 150-μm cap thickness. In contrast, another study found that postoperative refraction was not significantly affected by cap thickness of 100 and 120 μm in SMILE ( 11 ). In our study, cap thickness ranged from 110 to 140 μm, which may have led to different results.…”
Section: Discussionmentioning
confidence: 93%
“…There is a rising acceptance and recognition of SMILE surgery as a global surgical treatment option for refractive errors ( 4 ). Previous studies have reported that sex ( 5 ), age ( 6 , 7 ), preoperative spherical equivalent (SE) ( 8 ), corneal curvature ( 9 ), optical zone ( 10 ), central corneal thickness (CCT) ( 11 , 12 ), treatment nomogram ( 13 ), and laser energy ( 14 , 15 ) affect visual outcomes after SMILE. While previous studies mostly analyzed the influence of a single factor, in this study, machine learning was used to analyze 20 different factors to determine the most important factors affecting SMILE.…”
Section: Introductionmentioning
confidence: 99%
“…Although, the literature is controversial as to whether thicker caps result in biomechanically stronger 40 or weaker corneas. 41 Some recent publications even suggest a nomogram compensation based on the planned cap thickness. 42 …”
Section: Discussionmentioning
confidence: 99%
“…Caps were 140-150 µm thick, 43 the optical zone ranged from 5.5 to 6.5 mm, 44 the incision was positioned pseudo-superior at 150° with entry angle of 120° and width of 3.0 mm. 45 …”
Section: Discussionmentioning
confidence: 99%